Hacınlıyan Avadis - İnönü, Erdal (Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010)
TUMTMK XV. Ulusal Mekanik Kongresi, Komitemizin ilk üyelerinden merhum Prof. Dr. Erdal İnönü anısına düzenlenmiştir. Bu konuşmada kendisinin yaşamı ve katkıları, gençlerin bilime yönlendirilmesi ve ülkemizdeki bilimsel etkinliklerin geliştirilmesi üzerindeki etkileri vurgulanarak kısaca tanıtılmış, Kültür Üniversitesinde 21 Şubat 2007 tarihinde gerçekleştirilen Onursal Doktor unvanı takdimi törenindeki konuşması okunmuştur.

The Fifteenth National Mechanics Symposium organized by the Turkish National Committee on Pure and Applicd Mechanics has becn dedicated to the memory of the late Prof. Dr. Erdal İnönü, one of the fırst members of the Committee. His life and contributions have been presented with particular emphasis on his efforts in the development of scientific activities and encouragement of promising young students towards scientific work. His speech during the ceremony of presentation of the Honorary Doctorate on February 21, 2007 at Kültür University has also been read
Konferans Bildirisi -- Teorik ve Uygulamalı Mekanik Türk Milli Komitesi, 2010
Conference Paper -- Theoretical and Applied Mechanical Turkish National Committee, 2010